The origins of nonlinear enhancement in ex vivo tissue during high intensity focused ultrasound ablation. - Jackson, E; Cleveland, R; Coussios, C (2013)
Thermal ablation by high intensity focused ultrasound (HIFU) is an emerging technique for non-invasive treatment of tumors. One barrier to its wider use is that current imaging modalities are not able to directly monitor changes in the tissue during treatment. Nonlinear imaging has been suggested as a possible mode, but it is unclear whether the nonlinear enhancement is due to changes in the properties of treated tissue or cavitation. This study uses a finite-amplitude insertion technique to measure B/A of ex-vivo bovine liver as a function of temperature. The technique creates quasi-plane wave conditions by measuring the waveform in the near field of a 10 cm diameter 1 MHz unfocused source. The linear acoustic properties are measured in the same location and then B/A determined by fitting data to a numerical solution of the Burgers equation. Measurements are taken during heating in a water bath (at a slow rate) and HIFU exposure (at a fast rate). Cavitation is monitored during the HIFU exposures. Previous data suggested B/A doubles after heating. However, in these experiments, the changes were less than 20%. These data suggest that cavitation effects dominate changes in B/A.